A comparative assessment of decision to delivery interval for emergency and urgent lower segment caesarean section following maternal and foetal outcomes - Shishodiya, Madhu; Sachdev, Rakhi; Sudheshna Devi, Pothula; Bhadouriya, Amrita S.; Basu, Rakhi; Kamra, Sangeeta; Jacob, Shyla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Background: Timely decision-to-delivery interval (DDI) in lower segment caesarean section (LSCS) is critical for safeguarding maternal and foetal health. This study aimed to measure the DDI and assess its relationship with maternal and foetal outcomes. Methods: A prospective observational study was conducted among 361 deliveries at a tertiary care hospital in Bhilai, Chhattisgarh. Pregnant women undergoing emergency (Category 1, n=283) and urgent (Category 2, n=78) LSCS were enrolled. Maternal and foetal outcomes were evaluated. Results: A statistically significant difference was observed between mean DDI values in Category 1 and Category 2 (p<0.02). Maternal outcomes, including postpartum haemorrhage (PPH), post-operative fever, and blood transfusion, were significantly associated with increasing DDI (p<0.0001). A significant difference in neonatal intensive care unit (NICU) admission rates between the two categories was noted (p=0.03). APGAR score comparisons showed significant variations at different DDI intervals: 31–40 vs 51–60 min (p<0.0002), 41–50 min (p<0.00021) for 1-minute scores, and 21–30 min (p<0.028) for 5-minute scores. Conclusions: While increased DDI correlated with certain adverse maternal and neonatal outcomes (NICU admission and low APGAR scores), no critical maternal or foetal mortality was attributed directly to prolonged DDI.